Social insurance and the marriage market - Petra Persson (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
Social insurance is often linked to marriage. I model how such linkage affects the marriage market, and exploit Sweden's elimination of survivors insurance to demonstrate economically important responses along several behavioral margins in this market. Entry into marriage reflects a demand for survivors insurance up to 50 years before expected payout, especially among couples with high husband mortality risks. Further, elimination of survivors insurance induces divorces and intra-household redistribution towards wives in pre-existing marriages. Because survivors insurance subsidizes couples with highly unequal earnings (capacities), its elimination also raises the long-run assortativeness of matching. These findings demonstrate that when social insurance is linked to marriage, marital behavior is an integral component of couples' strategies to plan for financial security in old age. The magnitude of these marriage market responses influences the optimality of linking social insurance to marriage.
Keywords: J12; H31; D13; 330; Marriage; Social insurance; Cohabitation; Matching; Long-term financial planning